ANALISA FROUDE NUMBER EKONOMIS PADA KAPAL WISATA DI WADUK JATILUHUR DENGAN PENDEKATAN COMPUTATIONAL FLUID DYNAMIC (STUDI KASUS KM. JASATIRTA) - Samuel Samuel; Parlindungan Manik (TEKNIK, 2011)
Model catamarans increasingly popular as a means of transportation of goods and people that needdevelopment to find out more in the interaction prisoners on the ship hull in order to achieve stability and betterresistance. KM Jasatirta is one of ship model catamaran (double hull) which is designed to support tourism inJatiluhur Reservoir. This study aims to find out more details interaction of the total prisoners in the ship's hullKM Jasatirta with Computational Fluid Dynamics approach.Research carried out several stages of manufacture of the Computational Fluid Dynamic model, simulationinput data, running simulations to converge, then analyzes the results of calculations by the methodSlenderBody, Delft Series, 98, and CFD. Analysis of the calculation includes the analysis of resistance, FroudeNumber economic , and comparative analysis of numerical calculation by the method of Computational FluidDynamics.The results of the analysis and calculation of reseach showed that the total ship resistance (Rt) at 2 knots boatspeed by using the CFD method at 0.37 kN, Delft method Series'98 of 0.14 kN, while the calculation method forSlender Body 0.04 kN and a analityc calculation by the method of Millward's of 0215 kN. And based on theresults of analysis of Froude number of the most economical in terms of aspects of the ship's speed is the methodof Computational Fluid Dynamics with a value of 0094 sedangan Fn projection calculation with a quadraticfunction then the value of accurate Fn Series'98 Delft method so it can be used as a reference calculation.